Efektivitas Model Pembelajaran PjBL Berbantuan E-Linier terhadap Pemahaman Konsep dan Motivasi Belajar Siswa Materi SPLDV - Lestari, Mega Ayu; Tsani, Dyan Falasifa (Circle: Jurnal Pendidikan Matematika, 2024)
This study aims to evaluate the effectiveness of using project-based learning models supported by E-Linear in increasing students' understanding of concepts and learning motivation. Quantitative experimental methods were used with posttest only control group design. The research instrument consists of a learning motivation questionnaire and a posttest test. The study population included all grade VIII students of SMP N 18 Semarang, with samples selected using cluster random sampling techniques, namely experimental class (VIII B) and control class (VIII A). Data analysis involved Kolmogorov Smirnov's normality test with results of 0.109 and 0.144 for experimental and control classes, and Barlet's homogeneity test with results of 1.64. Hypothesis testing using the t test showed significant differences between experimental and control classes, with results of 7.94 for concept understanding and 5.59 for learning motivation. The results showed that the application of the Project Ba learning model.